Discourse Analysis of PB Djarum vs KPAI Polemic Reported by 3 Mass Media (CNN Indonesia, Detik, and Kompas.com) During the Period of September – October 2019 - Setiawan, Adeline; Daisy adela, brigitta (Jurnal Ilmu Sosial dan Humaniora, 2020)
This study analyzes and investigates several online news launched by 3 mass media (CNN Indonesia, Detik, and Tirto) related to PB Djarum vs KPAI Polemic in September 2019, using Van Dijk’s discourse analysis. It aims was to explore how different each article used its standpoints in reporting the issue, by looking at Text, Social Cognition, and Context dimensions. In text dimensions, it examines how the articles constructed through micro structure, super structure, and macro structure. Moreover, it is also trying to look beyond the written text, while analyzing in social cognition and context dimensions. This study concludes that the media, in this case the online news media, can be a powerful channel to influence readers through its construction of the polemic issue. As the tobacco industry still known as the main sponsor of badminton-coaching industry in Indonesia, most of the media were portraying positive image of PB Djarum.  Keywords: Discourse analysis, Mass Media, Text, Social Cognition, Context Dimension, Van Dijk’s,